CHANGES IN BLOOD GLUCOSE LEVELS IN EXPERIMENTAL ANIMALS WITH HYPERGLYCEMIA DUE TO LIME (Citrus aurantifolia Swingle) PEEL EXTRACT - Rivan Virlando Suryadinata (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Chronically elevated levels of glucose in the blood can lead to various complications. As a result, it can accelerate the damage to various organ tissues in the body. Several measures are needed to maintain the stability of normal blood glucose levels to prevent tissue damage, as well as providing additional intake such as lime peel extract which is believed to have high flavonoid content in lowering blood glucose levels. For this reason, this study aimed to analyse changes in blood glucose levels by giving lime extract to alloxan-induced experimental animals. This study uses an experimental post-test control group design. The results showed increased in blood glucose levels in the positive control group (p < 0.005). In addition, the lime (Citrus aurantifolia Swingle) peel extract treatment group showed changes in blood glucose levels (p < 0.005). It was concluded that increasing the intake of lime peel extract can reduce blood glucose levels.